Factors affecting the efficiency of logistics performance in Sapura Energy Berhad / Mas Diana Md Noor - Md Noor, Mas Diana (Faculty of Business and Management, 2018)
The title of this research study is “Factors Affecting Efficiency of Logistics Performance in Sapura Energy Berhad in Seri Kembangan”. Many did not aware of logistics department’s crucial role in an organization. Therefore, the objective of this study is to investigate the relationship between internal organizational communication and the logistics performance efficiency in an organization, to determine the relationship between advanced information technology and the logistics performance efficiency in an organization and to understand the level of employee competency affects the logistics performance efficiency in an organization. This study was also conducted in order to find the relationship between these variables. The three independent variables are organizational communication, advanced information technology and level of employee competency. In order to complete this study, three hypotheses are constructed, focused on determining the factors of the independent variables towards dependent variable. By using stratified random sampling, 105 questionnaires have been distributed among the staff in Supply Chain Management department in Sapura Energy Berhad, Seri Kembangan branch. All of the data obtained is analysed using reliability test, frequency testing, descriptive statistical test, Pearson Correlation coefficient and regression testing.